Emergency Department Provider Perspectives on Benzodiazepine–Opioid Coprescribing: A Qualitative Study. (19th September 2017) - Kim, Howard S.; McCarthy, Danielle M.; Hoppe, Jason A.; Mark Courtney, D.; Lambert, Bruce L.
Abstract: Objective: Benzodiazepines and opioids are prescribed simultaneously (i.e., "coprescribed") in many clinical settings, despite guidelines advising against this practice and mounting evidence that concomitant use of both medications increases overdose risk. This study sought to characterize the contexts in which benzodiazepine–opioid coprescribing occurs and providers' reasons for coprescribing. Methods: We conducted focus groups with emergency department (ED) providers (resident and attending physicians, advanced practice providers, and pharmacists) from three hospitals using semistructured interviews to elicit perspectives on benzodiazepine–opioid coprescribing. Discussions were audio‐recorded and transcribed. We performed qualitative content analysis of the resulting transcripts using a consensual qualitative research approach, aiming to identify priority categories that describe the phenomenon of benzodiazepine–opioid coprescribing. Results: Participants acknowledged coprescribing rarely and reluctantly and often provided specific discharge instructions when coprescribing. The decision to coprescribe is multifactorial, often isolated to specific clinical and situational contexts (e.g., low back pain, failed solitary opioid therapy) and strongly influenced by a provider's beliefs about the efficacy of combination therapy. The decision to coprescribe is further influenced by a self‐imposed pressure to escalate care or avoid hospital admission. When considering potential interventions to reduce the incidence of coprescribing, participants opposed computerized alerts but were supportive of a pharmacist‐assisted intervention. Many providers found the process of participating in peer discussions on prescribing habits to be beneficial. Conclusions: In this qualitative study of ED providers, we found that benzodiazepine–opioid coprescribing occurs in specific clinical and situational contexts, such as the treatment of low back pain or failed solitary opioid therapy. The decision to coprescribe is strongly influenced by a provider's beliefs and by self‐imposed pressure to escalate care or avoid admission.